2022
DOI: 10.3390/healthcare10050755
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage De-Identification Process for Privacy-Preserving Medical Image Analysis

Abstract: Identification and re-identification are two major security and privacy threats to medical imaging data. De-identification in DICOM medical data is essential to preserve the privacy of patients’ Personally Identifiable Information (PII) and requires a systematic approach. However, there is a lack of sufficient detail regarding the de-identification process of DICOM attributes, for example, what needs to be considered before removing a DICOM attribute. In this paper, we first highlight and review the key challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that de-identification process of DICOM attributes is important and some of them are required to be removed. Likely, a twostage de-identification process for medical images is available in DICOM file format [33]. This process must be taken into account in establishing further datasets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recent studies have shown that de-identification process of DICOM attributes is important and some of them are required to be removed. Likely, a twostage de-identification process for medical images is available in DICOM file format [33]. This process must be taken into account in establishing further datasets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This includes information on the modality used, scan parameters, patient information, and institutional information. This information is stored in a single file as metadata that can be accessed using tags [20]. Most tags have keywords to get specific information and its value.…”
Section: Methods 21 Dicom Standardmentioning
confidence: 99%
“…Leakage of important information can result in privacy violations, as well as 331 intrusion into the system [15], [16]. Therefore, tools are needed to protect sensitive information, one of which is the anonymization of DICOM [17]- [20]. While several tools are available for de-identifying DICOM data, including those integrated into DICOM Viewer software [21]- [24], many of these tools are commercial programs and may not be accessible to everyone.…”
Section: Introductionmentioning
confidence: 99%